Profesionalisme Tenaga Kesehatan dalam Penanganan Kegawatdaruratan COVID-19 - Fitriani Nur Damayanti; Budi Santosa; Ta’adi Ta’adi (Masyarakat Hukum Kesehatan Indonesia, 2022)
COVID-19 is an emergency that must be treated immediately by medical personnel. Handling the COVID-19 outbreak is the biggest challenge for health workers. Health workers need training for handling COVID-19 emergency cases because of the high risk in handling emergency cases. Patient safety is the main priority in handling emergency cases. The method used in this paper is a literature review study that aims to explore the professionalism of health workers in handling COVID-19 emergencies. The professionalism of health workers in handling COVID-19 emergencies consists of the main aspects, namely professional care in providing health services, competent health workers in handling COVID-19 emergencies, health workers having professional wisdom for handling COVID-19 emergencies, professional health workers having interpersonal competence, able to empower positive communication and partnerships with the patient's family, professional health workers develop themselves both personally and professionally, which is a prerequisite for true professionalism.